Renewable energy sources as a barrier to the EU’s common energy policy – on the example of Poland and Germany - Jankiewicz, Sławomir; Grądzik, Piotr (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
The main objective of the EU is to achieve a high rate of economic development. High rate of economic growth can be achieved, inter alia, by increasing economic cohesion. In the last period, the Community put special emphasis on the creation of a single electricity market. This market has led to lower prices, provided more secure supplies and facilitated the optimization of production plants based on renewable sources and thus their development. The aim of this article is a synthetic presentation of the problems that transmission system operators have with unscheduled electricity flows as a consequence of the production of renewable energy, which is difficult to predict. Solving this problem is crucial to the integration of the electricity market in the EU and thereby economic cohesion
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2017, Nr 466, s. 111-118
Keywords: cohesion policy; energy policy of EU; international power transmission systems; polityka spójności; polityka energetyczna UE; międzynarodowe systemy przesyłania energii